Protein enrichment of an Opuntia ficus-indica cladode hydrolysate by cultivation of Candida utilis and Kluyveromyces marxianus - Akanni, Gabriel B (J Sci Food Agric, 2015)
BACKGROUND: The cladodes of Opuntia ficus-indica (prickly pear cactus) have a low protein content; for use as a balanced feed, supplementation with other protein sources is therefore desirable. We investigated protein enrichment by cultivation of the yeasts Candida utilis and Kluyveromyces marxianus in an enzymatic hydrolysate of the cladode biomass. RESULTS: Dilute acid pretreatment and enzymatic hydrolysis of sun-dried cladodes resulted in a hydrolysate containing (per litre) 45.5 g glucose, 6.3 g xylose, 9.1 g galactose, 10.8 g arabinose and 9.6 g fructose. Even though K. marxianus had a much higher growth rate and utilized l-arabinose and d-galactose more completely than C. utilis, its biomass yield coefficient was lower due to ethanol and ethyl acetate production despite aerobic cultivation. Yeast cultivation more than doubled the protein content of the hydrolysate, with an essential amino acid profile superior to sorghum and millet grains. CONCLUSIONS: This K. marxianus strain was weakly Crabtree positive. Despite its low biomass yield, its performance compared well with C. utilis. This is the first report showing that the protein content and quality of O. ficus-indica cladode biomass could substantially be improved by yeast cultivation, including a comparative evaluation of C. utilis and K. marxianus. © 2014 The Authors. Journal of the Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.